Conservation and genetic analysis of the endangered Martina Franca donkey using pedigree data - Pierini, Claudia; Landi, Vincenzo; Ciani, Elena; Maggiolino, Aristide; Campanile, Domenico; Gomez Carpio, Mayra; De Palo, Pasquale (Frontiers in Animal Science, 2025)
IntroductionThe Martina Franca donkey is an endangered Italian breed with historical significance in agriculture and therapy. Conservation efforts are crucial due to increasing risks of genetic erosion and inbreeding.MethodsPedigree data from 2,261 individuals, spanning from 1940 to 2023, were analyzed. Key parameters such as inbreeding coefficients (FPED), effective population size (Ne), and founder contributions were computed using R packages including optiSel, purgeR, and pedigree. Population structure was assessed using demographic and genealogical indicators. ResultsThe study showed a rise in inbreeding (FPED increased from 0.07 in 2009 to 0.10 in 2020), with low Ne values (as low as 3.06 using complete generations), well below the FAO threshold (Ne > 50). Only 16.6 founders in the total population and 15.1 in the reference population accounted for most of the genetic diversity, indicating a genetic bottleneck. Despite recent demographic growth, mainly due to milk and therapy uses, genetic variability remains critically low. DiscussionThese findings highlight the need for immediate conservation strategies, including broadening the breeding base, limiting overuse of sires, and improving pedigree recording. Without intervention, the long-term viability of the breed is at risk.